Nicosia: una experiencia de arteterapia en un Centro de Día de Salud Mental - Amaya De Andrés Domínguez; Ana Iribas Rudín (Arteterapia)
This article describes the 2 ½-month-long project that the participants named Nicosia. It is part of a larger-scale art therapy project, in the Day Mental Health Centre of Majadahonda (Madrid, Spain), during 2006, and carried out by the authors. Their proposal was attended, and funds were obtained to make Nicosia into a book. Finally, the media repercussions of this fact are discussed.